"Sunset Carson rides again" - Drake, Oliver; Carson, Sunset, 1920-1990; Yucca Pictures Corporation; Cinetel Films ([Hollywood, CA] : Yucca Pictures, 1948)
Bo Ward comes to town to get the man who he thinks killed his father, his old friend Sunset Carson. But when he gets lost in the desert and drinks from a poisoned spring, who should save his life but the same Carson? As Ward gets better, he and Carson become close; Ward can hardly believe that this is actually the man who murdered his father, but he has his father's own letter to prove it. Later, when a mysterious outlaw breaks the wrist of the touring fighter Carson hired for an exhibition bout to raise money for a new school, Ward steps up to take on Murdoch, the evil foreman. Murdoch, it turns out, is involved in many more mysteries than just a fighter's broken wrist. With Ward's help, Carson soon gets to the bottom of them all, including the incriminating letter and who really killed Ward's father.
Sunset Carson, Al Terry, Pat Starling.
Photography, Clark Ramsey; editor, Ralph Dixon; music director, Frank Sanucci.
In English or Spanish.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed August 14, 2015)
Keywords: Western films; Feature films; Internet videos; Streaming video